Analysis on hydrodynamic interaction of two floating bodies with different dimensions using a hybrid two-way coupled field-domain decomposition method - Fujian LI; Xueqin LIU; Dan LI; Wei MENG; Zhuang KANG (Zhongguo Jianchuan Yanjiu)
ObjectivesDuring side-by-side operations of two floating bodies, significant wave oscillations within the gap and large-amplitude motion responses of the floating bodies can easily occur because of their proximity under hydrodynamic interactions, which pose serious threats to operational safety. Therefore, this study investigates the hydrodynamic interference characteristics between two floating bodies of different dimensions. MethodsA hybrid two-way coupled field-domain decomposition method was employed to establish a numerical wave tank, combined with the overset technology to simulate the motion characteristics of the two floating bodies. The study focused on the hydrodynamic interference between two floating bodies of different dimensions in regular waves. First, the hydrodynamic resonance phenomenon in the gap between two floating bodies of similar dimensions was numerically simulated and compared with experimental data to validate the accuracy of the numerical model. Subsequently, the heave motions of two floating bodies with different dimensions in regular waves were simulated, and the effects of different floating body arrangements on the vertical motion responses of the floating bodies were analyzed. ResultsThe results indicate that, the hybrid two-way coupled field-domain decomposition method, validated against experimental data, offers higher computational efficiency compared to the CFD method while maintaining accuracy. At high wave frequencies, the two floating bodies tend to exhibit anti-phase motion. Additionally, when the larger floating body is positioned upstream, it provides a significant shadowing for the smaller floating body downstream. ConclusionsThis study employs the hybrid two-way coupled field-domain decomposition method to validate the hydrodynamic interference model between two floating bodies. It reveals the occurrence of anti-phase motion of the two floating bodies at high wave frequencies and the shadowing effect when the larger floating body is upstream, providing theoretical guidance for optimizing floating body arrangements and enhancing operational safety.